Sociodemographic and training profile of nursing professionals in the state of São Paulo in relation to Integrative and Complementary Health Practices - Juliana Rizzo Gnatta; Thiago da Silva Domingos; Edilaine Cristina da Silva Gherardi-Donato; Suzimar de Fátima Benato Fusco; Leonice Fumiko Sato Kurebayashi; Talita Pavarini Borges (Universidade de São Paulo, 2024)
Objective: to analyze the sociodemographic and training profile of nursing professionals in the state of São Paulo in relation to Integrative and Complementary Practices in Health. Method: cross-sectional study, developed with 3,794 nursing professionals in the state of São Paulo, from 645 municipalities. To collect data, an online questionnaire was used containing sociodemographic and professional training variables. A hierarchical multiple Poisson regression model was constructed, considering training in practices as the dependent variable, with a significance level of 5%. Results: of the 3,794 (100%) participants, 479 (12.62%) had training in Integrative and Complementary Health Practices. The most frequent practices were auriculotherapy, Traditional Chinese Medicine/acupuncture and Reiki. The predominant training modalities were free, face-to-face and theoretical-practical courses. The variables age, no formal religion, higher education and specialization level, working hours and knowledge and previous experience on integrative practices were significant. Conclusion: the results indicate the need to encourage and expand the training of Integrative and Complementary Health Practices for nursing professionals, in order to strengthen their performance in health services.